What to Say When Things Get Tough: Business Communication Strategies for Winning People Over When They're Angry, Worried and Suspicious of Everything You Say (Audio Book) - Greenberger, Leonard (McGraw-Hill, 2013)
BREAK THROUGH ANYONE'S ANGER AND WIN THEIR TRUST IN CRISES LARGE AND SMALL Leonard S. Greenberger is a partner at one of today's most successful public relations firms. In What to Say When Things Get Tough , this seasoned expert offers verbal and nonverbal skills for handling communication crises in any public forum. "This book is one of the best guidebooks on the practice of public relations that I have seen." -- Jim Owen, Executive Director, Member Relations, Edison Electric Institute "If you want to learn why PowerPoint is a very poor way to present, why empathy works wonders, how positive messages, eye contact, and the right facial expressions can add up to make you overwhelmingly effective--or not--then this book is for you." -- Ari Weinzweig, cofounder and founding partner, Zingerman's, and author of Zingerman's Guide to Giving Great Service and Zingerman's Guide to Good Leading "Every business professional should have a copy on the shelf and pull it down whenever a tough situation presents itself." -- Win Porter, President, Waste Policy Center, former Assistant Administrator for Solid Waste and Emergency Response, U.S. Environmental Protection Agency.